Educommunication in adolescent students: radio and podcasts as instruments for sexual education: Uso de la radio y el podcast como instrumentos para la educación sexual - González-Quiñones, Fidel; Tarango, Javier; Castro-Cobos, Raul (Cuadernos de Documentación Multimedia, 2024)
Educommunication has become a solid discipline in the training of citizens in the face of the excess generation of media content and whose validity condition generates different disorders in communication ecosystems. This proposal presents results regarding the influence of the use of radio and podcasts as tools for teaching sexual education in young adolescents who attend Higher Secondary Education (EMS) in México, through a mixed-dominant quantitative type of research, based on a non-experimental design, whose analysis of the phenomenon is descriptive and transectional. The data collection comes from a probabilistic sampling of 348 participating subjects from five educational institutions located in a Mexican city with a marked influence of radio as a fundamental medium for content consumption by citizens. The study is divided into three sections: (1) sociodemographic data; (2) perceptions towards the sexual education received in the classroom; and (3) perceptions towards radio and podcasts as sexual education resources. The main findings of the research are oriented towards the high acceptance of the podcast as an effective means of promoting sexual education, above the radio and the training received in the classroom, classifying these options as low impact.
Keywords: Educommunication; sex education; podcast; radio; adolescent students; high school education